On co-operative modalities in the formulation of Mandarin Chinese turn-continuations - Lim, Ni-Eng (De Gruyter Mouton, 2021)
Multimodality (or the use of multiple resources to communicate) is not only a natural state of affairs in everyday communication, but is actually quite ubiquitous at all points within face-to-face interaction, ranging from the use of prosodic stress to denote focus, to emblematic gestures that convey specific meanings. Broadly speaking, such traditional construe of multimodality has often treated different modes of communication either as self-sufficient indexical signs; or working together as cumulatively ‘layered’ but semiotically discrete structures. However, Goodwin (2013) has shown how multimodality in natural interaction is in fact a highly integrated gestalt, where co-operative actions are being built by combining diverse resources in a way that both constrain and mutually elaborate each other. In this report, I focus on the action of constructing further talk as continuing past a possibly complete turn (a.k.a. turn-continuations) in Mandarin Chinese (henceforth Chinese), and argue how it constitutes a particularly rich environment for multiple systems of organization to “co-operate” in pursuit of interactional goals.